Pengembangan Desain Peningkatan Kapasitas Kader Posyandu dalam Pencegahan Stunting oleh Yayasan Usaha Mulia di Kabupaten Cianjur - Putri Milenia, Aprilia; Yuliani , Dwi; Irianti, Decky (Jurnal Ilmiah Kebijakan dan Pelayanan Pekerjaan Sosial (Biyan), 2024)
Cianjur Regency has a target for reducing stunting, namely zero stunting. Reducing the numbers on this target requires collaboration with cross sectors, one of which is the private sector. Yayasan Usaha Mulia (YUM) as one of the NGOs in Cianjur Regency has a stunting prevention program in collaboration with posyandu cadres and Community Leaders (CL). The aim of this research is to develop a technological engineering design to increase the capacity of posyandu cadres in preventing stunting. In this final design, there is material on stunting prevention, the role and rights of posyandu cadres, and steps to increase the capacity of posyandu cadres in stunting prevention behavior. The research method uses a qualitative approach with the Participatory Action Research (PAR) method. Data collection techniques through interviews, observation, documentation studies, and Focus Group Discussions (FGD). The research results show that developing a design to increase the capacity of posyandu cadres can be useful and facilitate the implementation of the stunting prevention program at YUM. This design contains important information related to stunting prevention in terms of developing capacity building such as pre-post-test, stunting prevention material, sharing sessions, group dynamics, social campaigns, and practical simulations. This design development was initiated by YUM as a sustainability program